Above‐ and below‐ground biomass and carbon dynamics in Brazilian Cerrado wet grasslands. (17th August 2012) - Fidelis, Alessandra; Lyra, Maria Fernanda di Santi; Pivello, Vânia Regina
Abstract: Questions: Grasslands are usually neglected as potential carbon stocks, partially due to the lack of studies on biomass and carbon dynamics in tropical grasslands. What is the importance of Brazilian tropical wet grasslands as carbon sinks? Does fire frequency and season affect biomass and carbon allocation in Brazilian wet grasslands? Location: Wet grasslands, tropical savanna, Jalapão, Tocantins, northern Brazil. Methods: We determined biomass above‐ and below‐ground, estimated carbon stocks in biennially burned plots (B2) and plots excluded from fire for 4 yr (B4). Moreover, we determined biomass in both rainy and dry seasons. Samples were 0.25 m × 0.25 m × 0.2 m (eight samples per treatment, applying a nested design, total of 48 samples). The biomass was classified in above‐ground graminoids, forbs and dead matter, and below‐ground roots and other below‐ground organs. We used ANOVA to compare variables between treatments and seasons. Results: More than 40% of the total biomass and carbon stocks were located below‐ground, mostly in roots. A high proportion of dead biomass (B4) was found in the above‐ground material, probably due to low decomposition rates and consequent accumulation over the years. Although these grasslands do not experience water stress, we found significant evidence of resource re‐allocation from below‐ground organs to the above‐ground biomass in the rainy season. Conclusions: We found more dead biomass in the rainy season, probably due to low decomposition rates, which can increase fire risk in these grasslands during the following dry season. These tropical wet grasslands stored high amounts of carbon (621 to 716 g C.m −2 ), mostly in the roots. Thus, policymakers should consider tropical grasslands as potential carbon stocks, since they are one of the most threatened and unprotected ecosystems in Brazil. Abstract : Fire plays an important role in Brazilian tropical savannas, affecting both above‐ and belowground biomass and carbon stocks. In this study we analysed the biomass and carbon dynamics from both above‐, and belowground according to different fire histories and season. Our results showed that these grasslands can store a large amount of carbon belowground and the longer the interval of fire, the higher the amount of dead biomass accumulated due to the low decomposition rates